Processamento por alta pressão hidrostática em frutas tropicais: inativação microbiológica e equivalência substancial - Binoti, Mirella Lima (2006)
The consumers has lived a very healthy life, which includes good meals, mainly with products as much as possible with natural, that gives the visual, nutritional and organoleptic characteristics, and above all that is safe in the microbiologic point of view. From these, we can stand HHP, because it is efficient to eliminate the microorganisms e enzymes that deteriorate the meals, causing minimum changes in the components of the flavors and nutrients. It is due to the treatment of high pressures to room temperature that only affects chemical bonds with non-covalent, while it leads intact the covalent bonds of small molecules, as in the majority of vitamins and volátics components which establishes a flavor to the fruit. This work deals with the efficiency of HHP in the conservation of the tropical fruit, (papaya and mangoes), analyzing a large part of factors that interfere in the quality of those juices macrobiotic and the substantial equivalent during 28 days in 4 and 28°C. The pulps were initially treated with 150 to 400 MPa pressure, for 10 minutes, and they were submitted to microbiological analyses. The result was a down growth of microorganisms proportionally to the value of the pressure applied. In order to obtain values of pressure and a minimum time of treatment, we selected the value of 400 MPa and submitted the pulp to a treatment for five minutes The value of the pressure of 400 MPa for 5 minutes was sufficient to eliminate the microorganisms that contaminate the pulps of the fruit we studied, for a period of 28 days, stored in 4 and 28°C, at the same time that the proprieties of substantial equivalence (C vitamin, Bcarotene, sugars, (solutes acids, pH and citric acidic) were kept in equal proportions or in advantage to the non-treated pulp. The majority of the analyzed factors under a 4°C temperature demonstrated a better conservation of the natural characteristics in relation to the stores pulps to 28°C. The results obtained demonstrate the efficiency of HHP in processing the pulps of papaya and mango and its advantages regarding the pasteurization.